Rancang Bangun Sistem Informasi Apotek Manajemen dan Penjualan Obat Berbasis Web - Akmal Hidayat; Azzahra Kusumanigtyas; Irmayana Irmayana; Lisah Febrianti; Nurfadilah Istiqamah; Hisdal Sikma Putra (PT. Lontara Digitech Indonesia, 2023)
This research aims to design and develop a web-based pharmacy information system to enhance efficiency and effectiveness of services in pharmacies. This web-based pharmacy information system has the potential to provide significant benefits in medication management, including accurate information about medications, improved inventory management, and enhanced patient care. The development method used in this research is the waterfall model, which includes stages such as requirements analysis, system design, coding, implementation, and testing. By using this method, the pharmacy information system was successfully designed and implemented, incorporating essential features such as medication data management, purchase and sales transactions, and reports that support efficient pharmacy management. The results of system testing show that the pharmacy information system functions well and meets expectations. This system facilitates users in managing medication data and transactions in the pharmacy. With this information system, pharmacy managers can operate their businesses more efficiently and provide better service to customers.